2021
DOI: 10.1101/2021.04.16.21255647
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prospective predictive performance comparison between Clinical Gestalt and validated COVID-19 mortality scores

Abstract: Background: Most COVID-19 mortality scores were developed in the early months of the pandemic and now available evidence-based interventions have helped reduce its lethality. It has not been evaluated if the original predictive performance of these scores holds true nor compared it against Clinical Gestalt predictions. We tested the current predictive accuracy of six COVID-19 scores and compared it with Clinical Gestalt predictions. Methods: 200 COVID-19 patients were enrolled in a tertiary hospital in Mexico … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…[12] In another study, several mortality scores (LOW-HARM, qSOFA, MSL-COVID-19, NUTRI-CoV and NEWS2) were compared according to physician's gestalt, and no score was found to be superior to the physician's gestalt. [13] In this study, physicians were found to be as successful as gestalt, and the CURB-65 score that every emergency medicine physician is familiar with consists of only five parameters that can be easily obtained (mainly obtained from vital signs). This has been confirmed in different populations and has been acknowledged as a strong predictor of mortality in pneumonia patients.…”
Section: Discussionmentioning
confidence: 87%
“…[12] In another study, several mortality scores (LOW-HARM, qSOFA, MSL-COVID-19, NUTRI-CoV and NEWS2) were compared according to physician's gestalt, and no score was found to be superior to the physician's gestalt. [13] In this study, physicians were found to be as successful as gestalt, and the CURB-65 score that every emergency medicine physician is familiar with consists of only five parameters that can be easily obtained (mainly obtained from vital signs). This has been confirmed in different populations and has been acknowledged as a strong predictor of mortality in pneumonia patients.…”
Section: Discussionmentioning
confidence: 87%
“…The value of the clinical gestalt as a diagnostic tool has been studied in different health conditions (10)(11)(12)(13). In acute coronary syndrome, heart failure, pneumonia, and COVID-19, the clinical gestalt registered by doctors was comparable to clinical scores in "ruling in" or "ruling out" patients with certain symptoms presenting to the ED (10)(11)(12)(13)(14). For sepsis, the Third International Consensus Definitions for Sepsis and Septic Shock (Sepsis-3) advocates clinicians should, in addition to systemic inflammatory response syndrome (SIRS) criteria, use clinical gestalt in screening, treating and risk-stratifying patients with infection (15).…”
Section: Introductionmentioning
confidence: 99%